PEMBUATAN ETANOL DARI UMBI GARUT (Maranta arundinacea) SECARA HIDROLISIS ENZIMATIS DENGAN PENAMBAHAN NPK SEBAGAI NUTRISI FERMENTASI MENGGUNAKAN Saccharomyces cerevisiae - Wulan Verani; Rudi Kartika; Winni Astuti (PROSIDING SEMINAR KIMIA, 2018)
Ethanol production as a biofuels successor fossil fuels from arrowroot tubers (Maranta arundinacea) through enzymatic hydrolysis process and fermentation use Saccharomyces cerevisiae has been carried out. This research aimed to determine levels of ethanol production by various concentration of nutrients added and variations time of fermentation. Hydrolysis process by enzymatic through a liquefaction phase with α-amylase and gluco-amylase at the saccharification stage. In the fermentation process NPK is used as a fermentation nutrient. The variations of NPK used is 1%, 2% and 3% (w/v) and the variations of fermentation time is 5, 7 and 9 days. The highest ethanol concentration of ethanol obtained are in addition of NPK nutrition at 2% (w/v) for 7 days, with the obtained ethanol concentration of 46, 989%. Keywords: ethanol, arrowroot tubers (Maranta arundinacea), NPK, fermentation.